About the equivalent level of flight safety - B. I. Bachkalo; V. I. Zolotykh (Научный вестник МГТУ ГА)
The article analyzes the meaning of the term "equivalent flight safety". The need for such an analysis is due to the fact that there is no definition of this term in the guidance documents on engineering and aerodrome flight support. This creates the ambiguous interpretation of the meaning embedded in this term and the possibility of non-compliance with the necessary flight safety measures at the aerodrome. As a result of the analysis, the expediency of the use of the term "equivalent level of flight safety" when determining the aerodrome operational suitability is substantiated. Management of the state of the aviation system from the point of view of information theory is considered. As a result, it was established that the ability to assess the impact of each element of the aviation system on its security against the effects of hazardous factors makes it possible to increase the efficiency of managing the state of this security. Dependence of the aerodrome flight safety level on the legality of the aerodrome operation is shown. The feasibility of achieving the equivalent level of flight safety using a new indicator, the equivalence coefficient, is substantiated. The formula that allows to calculate this indicator is derived. The numerical value of the equivalence coefficient depends on the values of the coefficients of compliance with the aerodromes operational suitability standards. The minimal set of evaluated elements is shown which determines the value of each coefficient of compliance with the aerodromes operational suitability standards. A mathematical model that reflects the dependence of the coefficient of compliance value with the operational suitability standards on the estimated indicators is constructed. The coefficients and indicators considered in the article in aggregate represent a new approach to assessing the level of aerodrome flight safety. This approach can be successfully applied in assessing the level of flight safety by any element of the aviation system.